The GPI-anchored 6-Cys Protein Pv12 is Present in Detergent-resistant Microdomains of Plasmodium vivax Blood Stage Schizonts (2013)
Plasmodium vivax malaria remains one of the tropical diseases causing an enormous burden on global public health. Several proteins located on this parasite species' merozoite surface have been considered the most suitable antigens for being included in an anti-malarial vaccine, given the functional role they play during the parasite's interaction with red blood cells. The present study identifies and characterizes the P. vivax Pv12 surface protein which was evaluated by using molecular biology and immunochemistry assays; its antigenic potential was also examined in natural and experimental P. vivax malaria infections. The P. vivax VCG-1 strain Pv12 gene encodes a 362 amino acid-long protein exhibiting a signal peptide, a glycosylphosphatidylinositol (GPI) anchor sequence and two 6-Cys domains. The presence of the Pv12 protein on the parasite's surface and its association with detergent-resistant membrane complexes, together with its antigenic potential, supports the notion that this antigen could play an important role as a red blood cell binding ligand. Further studies aimed at establishing the immunogenicity and protection-inducing ability of the Pv12 protein or its products in the Aotus experimental model are thus suggested. © 2012 Elsevier GmbH.